2019
DOI: 10.1371/journal.pbio.3000456
|View full text |Cite
|
Sign up to set email alerts
|

The lunar cycle drives migration of a nocturnal bird

Abstract: Every year, billions of seasonal migrants connect continents by transporting nutrients, energy, and pathogens between distant communities and ecosystems. For animals that power their movements by endogenous energy stores, the daily energy intake rates strongly influence the speed of migration. If access to food resources varies cyclically over the season, migrants sensitive to changes in daily energy intake rates may adjust timing of migration accordingly. As an effect, individuals adjusting to a common tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 36 publications
(59 reference statements)
3
39
0
Order By: Relevance
“…5I) and also well visible in the circular analyses (Fig. 5E-G): Wildtype siblings and heterozygous worms distribute their spawning across a lunar month significantly different from random (Rayleigh test p=1.75x10 10 and p=3.13x10 8 ), but with rather low phase coherence, i.e. population synchrony (r=0.295 and r=0.222), consistent with the wildtype data from the phase shift experiment (Fig.…”
Section: L-cry Mutants Show Altered Lunar Spawning Synchronysupporting
confidence: 82%
See 1 more Smart Citation
“…5I) and also well visible in the circular analyses (Fig. 5E-G): Wildtype siblings and heterozygous worms distribute their spawning across a lunar month significantly different from random (Rayleigh test p=1.75x10 10 and p=3.13x10 8 ), but with rather low phase coherence, i.e. population synchrony (r=0.295 and r=0.222), consistent with the wildtype data from the phase shift experiment (Fig.…”
Section: L-cry Mutants Show Altered Lunar Spawning Synchronysupporting
confidence: 82%
“…Starting with the early 20th century, numerous scientific studies have shown that the reproductive behavior and sexual maturation of animals as diverse as corals, polychaetes, echinoderms, fishes or turtles are synchronized by the lunar cycle (1,(3)(4)(5)(6)(7). A recent study suggests that the lunar cycle coordinates the behaviour of a nocturnal migratory bird (8), and recently uncovered clear correlations of human sleep and menstrual cycle properties with moon phases have re-initiated the discussion of an impact of the moon even on human biology (9,10). In animals, these synchronizations are not only impressive, but typically also important to ensure successful reproduction (11).…”
Section: Main Textmentioning
confidence: 99%
“…In addition, recent findings from the European Nightjar call attention to yet another temporal domain that may have been largely overlooked, at least in landbirds. Nocturnally migratory nightjars time fueling and migration events to the different phases of the moon (Norevik et al, 2019), and thereby call for further studies of moon cycle effects on migratory birds, ideally with a circannual perspective (Chapin and Wing, 1959;Cruz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, we still need to understand exactly how the endogenous migration program interacts with external information, and how birds keep track of space during long migrations throughout the annual cycle. A successful research agenda may be to combine an experimental approach (e.g., Kishkinev et al, 2015;Willemoes et al, 2015;Wikelski et al, 2015;Ilieva et al, 2018) with advanced tracking in the wild (e.g., Willemoes et al, 2014;Bäckman et al, 2017;Sokolovskis et al, 2018;Norevik et al, 2019).…”
Section: Variation In Migration Programsmentioning
confidence: 99%
“…Each year, billions of seasonal migrants connect the continents, transporting different substances, energy and pathogens between remote communities and ecosystems. Migratory animals change ecology and ecosystems by transporting energy, nutrients and living organisms, as well as by extracting food and becoming prey (Bauer & Hoye, 2014;Zaifman et al, 2017;Norevik et al, 2019;Koshelev et al, 2020). Consequently, migratory species profoundly alter the dynamics of trophic connections, biocenosis processes and ecosystem functioning as a unique and highly influential component of local biocenosis diversity.…”
Section: Introductionmentioning
confidence: 99%